Development of Local Food SMEs From Processed Mocaf Flour (Modified Cassava Flour) in Bojong Neros Village Curug, Bogor City - Raini, Yeni; Maimunah, Maimunah (LPPM Univ. Ibn Khaldun Bogor, 2022)
The Covid-19 pandemic that occurred had a negative impact on the MSMEs sector because MSMEs players experienced a decline in market demand. In line with these conditions, technological developments in the Industrial Era 4.0 also require business actors including MSMEs to adapt and adapt to existing conditions. Due to changes in people's consumption patterns due to the WFH (Work From Home) and PSBB policies from conventional shopping patterns to online shopping patterns, this is a challenge as well as an opportunity for MSMEs actors in marketing their products. The purpose of this service is to provide assistance in managing food made from mocaf flour and provide training on the application of digital business using LaDaRa e-commerce for product marketing activities for MSMEs in Bojong Neros Village, Curug Bogor, which have been affected by the pandemic. The method used in mentoring MSMEs actors is to provide training to make processed food made from mocaf flour, through an observation approach, analysis of partner needs, lectures, discussions, and tutorials on using the LaDaRa Marketplace application. MSMEs actors who processed mocaf flour in Bojong Neros Village, Curug Bogor can understand how to make food made from mocaf flour and the importance of online marketing which is expected to increase sales volume and family income.